2020
DOI: 10.3390/s20247236
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Knitted and Stitched Textile Strain Sensors

Abstract: By embedding conductive yarns in, or onto, knitted textile fabrics, simple but robust stretch sensor garments can be manufactured. In that way resistance based sensors can be fully integrated in textiles without compromising wearing comfort, stretchiness, washability, and ease of use in daily life. The many studies on such textile strain sensors that have been published in recent years show that these sensors work in principle, but closer inspection reveals that many of them still have severe practical limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…Hysteresis values can be calculated along the resistance axis (vertical) or along the strain axis (horizontal), and these values will be referred to as resistance hysteresis and strain hysteresis , respectively [ 18 ]. For a strain gauge in an application, the expected errors in the measured strain are of primary concern; thus, as a performance indicator, we prefer to use the strain hysteresis values and not the more commonly reported resistance hysteresis [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hysteresis values can be calculated along the resistance axis (vertical) or along the strain axis (horizontal), and these values will be referred to as resistance hysteresis and strain hysteresis , respectively [ 18 ]. For a strain gauge in an application, the expected errors in the measured strain are of primary concern; thus, as a performance indicator, we prefer to use the strain hysteresis values and not the more commonly reported resistance hysteresis [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Liang et al also remark that a promising way to reduce hysteresis is to use Eeontex in the sensor base structure [ 14 ]. The resistivities of the currently available conductive yarns vary widely, and the study of Raji et al [ 17 ] seems to suggest that sensors with conductive yarn with a resistance of 77 ohm/cm have an optimum GF in the resistance range of 40 to 120 ohms, but the effect was not studied in detail [ 18 ]. The type of knit design is another essential parameter that affects the sensor performance, and many different studies to investigate the effect on sensor performance were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hysteresis values were calculated as the maximum strain difference between stretched and unstretched cycles, scaled to the working range. The working range defines the maximum and minimum strain values that can be measured by the sensor [5].…”
Section: B Measurement Techniquesmentioning
confidence: 99%
“…Strain sensors commonly used for mechanical engineering applications are typically limited to strain not larger than 1 %. For the on-body applications, we need to be able to measure strains up to 30-40% [5]. In addition, for unobtrusive monitoring of the sensors need to be breathable, washable, and stretchable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation